Analysis Student's Comprehension in Reading Narrative Text on English Learning at Junior High School: Analisis Pemahaman Siswa Dalam Membaca Teks Naratif pada Pelajaran Bahasa Inggris Di SMP - Gita Dwi Setyawati; Vidya Mandarani (Universitas Muhammadiyah Sidoarjo, 2021)
Indonesia become is one of the nations which have characteristics almost of community not like reading activity. There is a number of advantages that can be picked when applied reading habits in life. Therefore, researchers are very interested in using research topics related to students' comprehension of reading skills. This study examines more deeply the factors that cause students to have difficulty in understanding the narrative text in English lessons. This type of research is qualitative research that involves descriptive information while the use of the method is more than one such as observation, interview, and documentation. The results of this study indicate that students have difficulty in reading narrative texts because of internal and external factors.